Two new lignans from the aerial part of Vitex negundo. Issue 7 (2nd July 2016) - Nie, Xiu-Fang; Yu, Li-Li; Tao, Yuan; Huang, Jian; Ding, Li-Qin; Feng, Xin-Chi; Jiang, Miao-Miao; Zheng, Lin; Chen, Li-Xia; Qiu, Feng
Abstract: A new phenyldihydronaphthalene-type lignan, (3 R, 4 S )-6-hydroxy-4-(4-hydroxy- 3-methoxyphenyl)-5, 7-dimethoxy-3, 4-dihydro-2-naphthaldehyde-3 a - O - β -d -glucopyranoside (1 ), and a new phenylnaphthalene-type lignan, 6, 7, 4′-trihydroxy-3′-methoxy-2, 3- cycloligna-1, 4-dien-2 a, 3 a -olide (2 ), along with 10-known lignan derivatives (3 –12 ) were isolated from the aerial part of Vitex negundo var. heterophylla. Their structures were established by comprehensive 1D- and 2D-NMR spectroscopic analyses.